Impact of the malnutrition on mortality in Rheumatoid arthritis patients: A cohort study from NHANES 1999–2014 - Tian, Pan; Xiong, Jialing; Wu, Wanxia; Shi, Shanshan; Chen, Aizhen; Chen, Kaihong; Chen, Weihua; Wu, Aiyu; Liao, Ying (Frontiers in Nutrition, 2023)
Abstract Background: Patients with Rheumatoid arthritis (RA) are prone to malnutrition. However, it is rare studies assessing the relationship between malnutrition and all-cause mortality in patients with RA. Objective: To investigate the relationship between malnutrition and all-cause mortality in patients with RA in a large national sample cohort. Methods: We analyzed data on 1,976 adults ≥ 18 years of age during National Health and Nutrition Examination Survey (NHANES) 1999-2014. We chose the Controlled Nutritional Status Score (CONUT) and the Nutritional Risk Index (NRI) to assess the nutritional status of patients with RA. The Kaplan–Meier (KM) survival curves Cox proportional hazards regression models were used to analyze the associations between malnutrition and all-cause mortality. Results: Of the 1,976 patients with RA (57.38 ± 0.40 years, female 59.9%, non-Hispanic white 69.9%), the prevalence of malnutrition was 18.8% by used the CONUT and 26.6% by used the NRI. The KM survival curves showed that malnutrition was associated with a higher incidence of all-cause mortality during the 10-year follow-up period (log-rank test, P < 0.001). In the fully corrected model, the adjusting hazard ratio (aHR) for all-cause mortality in patients with moderate to severe malnutrition with CONUT and NRI were 5.63 (95% CI, 2.55-12.45; P < 0.001) and 2.56 (95% CI, 1.81-3.62; P < 0.001) respectively, compared with patients without malnutrition. Conclusions: Malnutrition is very prevalent in patients with RA, approximately 1/5 to 1/4. Malnutrition is strongly associated with an increased risk of all-cause mortality. These findings underscore the importance of attention and intervention in the nutritional status of patients with RA. Further clinical trials are needed to prospectively assess the effect of nutritional interventions on the prognosis of patients with RA.